IPGRI in Asia, the Pacific and Oceania: Regional report - APO 1999-2000 - International Plant Genetic Resources Institute (2001)
This report highlights some particularly significant achievements of IPGRI's activities in Asia, the Pacific and Oceania in1999–2000 and describes the impact that this work is having. It summarizes some of IPGRI's recent activities in the region, carried out with its numerous partners in the governmental, non-governmental and private sectors. The activities were identified as priority areas for attention through consultations with national and regional plant genetic resources networks and with specific crop networks. IPGRI's work contributes to three objectives: - strengthened national capacities, particularly in developing countries, to conserve, access and use genetic resources; - international collaboration in the conservation and use of plant genetic resources; and - generation and use of knowledge and technologies relevant to improved conservation and use of plant genetic resources.